2021
DOI: 10.1111/scd.12643
|View full text |Cite
|
Sign up to set email alerts
|

Ludwig's angina in a COVID positive patient—An atypical case report

Abstract: The management of odontogenic infections is established and several guidelines have been proposed for its effective treatment. Outbreak of COVID-19 has posed serious challenge in the management of odontogenic infections, further complicated by immunocompromised status of the patient, where adequate evaluation and prompt attention is mandatory to avoid untoward consequences. Ludwig's angina being a life threatening infection by itself, association or simultaneous presentation with COVID-19 infection can add fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Its progression to adjacent areas can lead to airway obstruction, necessitating emergent intervention. Odontogenic infections are the most common cause, accounting for 70% to 90% of cases [4][5][6]. The premolar is the most frequently implicated site of origin for Ludwig's angina [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its progression to adjacent areas can lead to airway obstruction, necessitating emergent intervention. Odontogenic infections are the most common cause, accounting for 70% to 90% of cases [4][5][6]. The premolar is the most frequently implicated site of origin for Ludwig's angina [7].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response following this procedure penetrated the sublingual ridge into the submandibular space, leading to significant clinical symptoms in this patient. Other causes of severe submandibular space infection include mouth floor trauma, sialadenitis, mandibular fractures, tonsillopharyngitis, and tongue piercings [3,4,7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cardiac arrest complications occur more frequently following difficult intubation 14. Blind nasal intubation is not suggested due to the risk of abscess rupture 15. If endotracheal intubation cannot be done in these patients, surgical airway management is recommended 16…”
Section: Discussionmentioning
confidence: 99%
“… 14 Blind nasal intubation is not suggested due to the risk of abscess rupture. 15 If endotracheal intubation cannot be done in these patients, surgical airway management is recommended. 16 …”
Section: Discussionmentioning
confidence: 99%